Role of plant metabolites in the formation of bacterial communities in the rhizosphere of Tetrastigma hemsleyanum - Huang, Yuqing; Hu, Hongliang; Yue, Erkui; Ying, Wu; Niu, Tianxin; Yan, Jianli; Lu, Qiujun; Ruan, Songlin (Frontiers in Microbiology, 2023)
Tetrastigma hemsleyanum Diels et Gilg, commonly known as Sanyeqing (SYQ), is an important traditional Chinese medicine. The content of bioactive constituents varies in different cultivars of SYQ. In the plant growth related researches, rhizosphere microbiome has gained significant attention. However, the role of bacterial communities in the accumulation of metabolites in plants have not been investigated.Herein, the composition of bacterial communities in the rhizosphere soils and the metabolites profile of different SYQ cultivars' roots were analyzed. It was found that the composition of microbial communities varied in the rhizosphere soils of different SYQ cultivars. The high abundance of Actinomadura, Streptomyces and other bacteria was found to be associated with the metabolites profile of SYQ roots. The findings suggest that the upregulation of rutin and hesperetin may contribute to the high bioactive constituent in SYQ roots. These results provide better understanding of the metabolite accumulation pattern in SYQ, and also provide a solution for enhancing the quality of SYQ by application of suitable microbial consortia.